Widespread Increases in Malondialdehyde Immunoreactivity in Dopamine-Rich and Dopamine-Poor Regions of Rat Brain Following Multiple, High Doses of Methamphetamine - Horner, Kristen Ashley; Gilbert, Yamiece E.; Cline, Susan D. (Frontiers in Systems Neuroscience, 2011)
Treatment with multiple high doses of methamphetamine (METH) can induce oxidative damage, including dopamine (DA)-mediated reactive oxygen species (ROS) formation, which may contribute to the neurotoxic damage of monoamine neurons and long-term depletion of DA in the caudate putamen (CPu) and substantia nigra pars compacta (SNpc). Malondialdehyde (MDA), a product of lipid peroxidation by ROS, is commonly used as a marker of oxidative damage and treatment with multiple high doses of METH increases MDA reactivity in the CPu of humans and experimental animals. Recent data indicate that MDA itself may contribute to the destruction of DA neurons, as MDA causes the accumulation of toxic intermediates of DA metabolism via its chemical modification of the enzymes necessary for the breakdown of DA. However, it has been shown that in human METH abusers there is also increased MDA reactivity in the frontal cortex, which receives relatively fewer DA afferents than the CPu. These data suggest that METH may induce neuronal damage regardless of the regional density of DA or origin of DA input. The goal of the current study was to examine the modification of proteins by MDA in the DA-rich nigrostriatal and mesoaccumbal systems, as well as the less DA-dense cortex and hippocampus following a neurotoxic regimen of METH treatment. Animals were treated with METH (10 mg/kg) every 2h for 6h, sacrificed one week later, and examined using immunocytochemistry for changes in MDA-adducted proteins. Multiple, high doses of METH significantly increased MDA immunoreactivity (MDA-ir) in the CPu, SNpc, cortex and hippocampus. Multiple METH administration also increased MDA-ir in the ventral tegmental area (VTA) and nucleus accumbens (NAc). Our data indicate that multiple METH treatment can induce persistent and widespread neuronal damage that may not necessarily be limited to the nigrostriatal DA system.